Cross-Sectional Assessment of Antibiotic Prophylaxis Practices and Their Association with Surgical Site Infection Rates - Dr. Vamshi Krishna Gorle, Dr Phani Kumar M, Dr Sabir Pasha Md (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Surgical Site Infections (SSIs) remain a leading cause of postoperative morbidityand prolonged hospital stay, often influenced by inappropriate antibiotic prophylaxis practices.Despite established international guidelines, adherence in clinical settings varies widely,especially between elective